Subjective Responses to Various Filling Solutions in the Posterior Fluid Reservoir of Miniscleral Lenses at Application. Issue 2 (February 2022) - Tan, Jacqueline; Peguda, Rajini; Siddireddy, Jaya Sowjanya; Briggs, Nancy; Stapleton, Fiona
Abstract : Purpose: To compare the effect of the use of different lubrication eye drops and nonpreserved saline for the application of miniscleral contact lenses (CLs) on subjective experience during 6 hr of lens wear. Methods: Experienced soft CL wearers aged 18 to 45 years (inclusive) were enrolled in this prospective, randomized, double-masked, three arm comparison cross-over study. Subjects were custom fitted with KATT 16.5 mm diameter miniscleral lenses, ordered to their prescription. Subjects attended visits on three separate days and were randomized to receive instillation of an HP-guar/nanoemulsion drop or an HP-guar/sodium hyaluronate (HA) eye drop into the miniscleral lens before filling with saline or filling with saline alone (control). Subjective responses were collected up to 6 hr postapplication. Generalized linear mixed models with multinomial distribution and cumulative logit link were used to compare the rate at which responses improved post-CL application for the different treatments. Results: Twenty-four participants completed the study. Dryness symptoms were more likely to improve at a slower rate postlens application with saline alone compared with the addition of HP-guar/nanoemulsion ( P =0.005) or HP-guar/HA ( P =0.049) before lens application. Furthermore, the addition of HP-guar/nanoemulsion was more effective than saline alone in improving symptoms of fluctuating vision ( P =0.011), grittiness/burning/stinging ( P =0.001), and foreign body sensation ( P =0.006) more quickly. Conclusions: The use of postlens lubrication may be useful in enhancing adaptation to miniscleral lenses.